2009
DOI: 10.1093/nar/gkp700
|View full text |Cite
|
Sign up to set email alerts
|

CpG methylation potentiates pixantrone and doxorubicin-induced DNA damage and is a marker of drug sensitivity

Abstract: DNA methylation is an epigenetic modification of the mammalian genome that occurs predominantly at cytosine residues of the CpG dinucleotide. Following formaldehyde activation, pixantrone alkylates DNA and particularly favours the CpG motif. Aberrations in CpG methylation patterns are a feature of most cancer types, a characteristic that may determine their susceptibility to specific drug treatments. Given their common target, DNA methylation may modulate the DNA damage induced by formaldehyde-activated pixant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…DNA methylation level from CpG islands linked to twenty eight genes whose expression levels had been shown to contribute with the resistance against DNA double strand break induced drugs. These data were supported in some way to our data in documenting DNA methylation by different doses of doxorubicin drug in non-tumor female mice [28] assessed the CpG methylation aberrations induced by pixantrone and doxorubicin. A characteristic that may determine the most cancer types to specific drug treatments and is a marker of drug sensitivity.…”
Section: Discussionsupporting
confidence: 79%
“…DNA methylation level from CpG islands linked to twenty eight genes whose expression levels had been shown to contribute with the resistance against DNA double strand break induced drugs. These data were supported in some way to our data in documenting DNA methylation by different doses of doxorubicin drug in non-tumor female mice [28] assessed the CpG methylation aberrations induced by pixantrone and doxorubicin. A characteristic that may determine the most cancer types to specific drug treatments and is a marker of drug sensitivity.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, it is known that, in cancer cells, the mode of action of PIX was not confined to inhibiting topoisomerase II, but extended to forming PIX-formaldehyde conjugates that crosslinked to DNA much more efficaciously than equivalent DOX conjugates (Evison et al, 2009;Cell Therapeutics Inc., 2012). This anticipates that, in cancer cells altered by prior waves of DOX clearance, a limited uptake of PIX would be outweighed by its greater potency in damaging DNA.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, it has been shown that pixantrone intercalates from the DNA major groove [19]. However, evidence of minor groove association was also observed.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Its novel mode of action offers a reduced potential for generating reactive oxygen species, binding iron and forming alcohol metabolites that cause the cardiac toxicity of anthracycline [14,17,18]. Moreover, it has been demonstrated that CpG methylation, which is specific to tumour cells, augments the generation of covalent pixantrone--DNA adducts [19].…”
Section: Pharmacodynamicsmentioning
confidence: 99%